2013
DOI: 10.1136/vr.101083
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of African horse sickness in Senegal, and methods of control of the 2007 epidemic

Abstract: Since first being detected in Nigeria in January 2007, African horse sickness virus serotype 2 (AHSV-2) has spread throughout the northern hemisphere, and was first reported in Senegal. A retrospective study was conducted from December 2009 to April 2010 using data collected in the field combined with information available at the Direction of Veterinary Services. The epidemic started in the Dakar region with two outbreaks in March and June 2007, respectively, and spread in several parts of the country between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 20 publications
0
48
0
Order By: Relevance
“…The distribution of C. imicola , especially in southern Europe, is an old and actual subject of interest as illustrated by AHS and BT history: AHS is endemic in areas of Sub-Saharan Africa, as highlighted by the recent outbreaks in Senegal in 2007 [1], and has sporadically caused devastating outbreaks outside Africa, eg. in 1959–61 in the Middle East and in Asia (where over 300 000 equids died), and in 1987–90 on the Iberian Peninsula [7].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of C. imicola , especially in southern Europe, is an old and actual subject of interest as illustrated by AHS and BT history: AHS is endemic in areas of Sub-Saharan Africa, as highlighted by the recent outbreaks in Senegal in 2007 [1], and has sporadically caused devastating outbreaks outside Africa, eg. in 1959–61 in the Middle East and in Asia (where over 300 000 equids died), and in 1987–90 on the Iberian Peninsula [7].…”
Section: Introductionmentioning
confidence: 99%
“…The country faced outbreaks of African horse sickness (AHS) in 2007 which caused the death of 1169 horses and considerable economic losses, estimated to 1.4 million euros [43, 44]. …”
Section: Introductionmentioning
confidence: 99%
“…26 A retrospective study of the 2007 AHS epidemic in Senegal identified AHSV-2 as the serotype responsible for the outbreak and mortality in horses. 27 …”
mentioning
confidence: 97%
“…25 AHS is endemic in many countries in central and eastern Africa and spreads regularly to southern Africa. 9,[26][27][28][29][30] In endemic areas, different serotypes may be active simultaneously, but one serotype is usually dominant during a particular season. The disease is occasionally reported in countries in North Africa, from where it has also entered the Middle East and Spain.…”
mentioning
confidence: 99%